Efikasi diri dan Motivasi Belajar: Pengaruhnya terhadap Kemandirian Belajar Siswa MTs Bi’rul Ulum Gemurung Gedangan Sidoarjo - Bayhaqi, Hasmi Nur; Badriyah, Laila (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
As an ability that every individual student must have according to the rules of the national education system, learning independence includes the ability to learn independently and develop their personal abilities. However, in reality the world of education in Indonesia is still relatively low and many students lack the ability to learn independently. This research highlights the urgency of increasing student learning independence as a solution to ensuring educational success in an era full of complexity and rapid change. Descriptive quantitative with correlative or correlational research methods is this research approach. The research population was all 102 MTs Bi'rul Ulum students with a sample of 36 taken using random sampling techniques. A closed questionnaire is used as a means of collecting data in the form of a likert scale. In the research results, it is known that self-efficacy has more influence on learning independence than learning motivation. The results show that self-efficacy has a significant effect on learning outcomes, learning motivation also has a significant effect on learning independence, and self-efficacy and learning motivation are also known to have an effect on learning independence. The higher a student's level of self-efficacy, the more their learning independence will increase. In addition, learning motivation encourages students to learn with enthusiasm and curiosity, thereby increasing their learning independence. Students who have high learning motivation will tend to be interested in exploring various topics and learning materials independently, without having to rely on instructions from teachers or encouragement from parents.